Dopa-responsive dystonia - Đurić Gordana; Svetel Marina; Džoljić Eleonora; Kostić Vladimir (Vojnosanitetski Pregled)
Backgrround/Aim. Dystonia is considered to be a prolonged involuntary contractions of the muscles leading to twisting, repetitive movements or irregular postures. Etiologically, it could be classified as primary and secondary dystonia. Dopa-responsive dystonia (DRD) belongs to a group of primary dystonia. The aim of this study was to detect the presence of gene GCH-I mutation in our population in patients with dopa-responsive dystonic dyskinesia and to analyze clinical specificity of the affected. Methods. Out of the group of patients with dystonia of different distribution four patients were separated whose clinical picture indicated the diagnosis of DRD. Two patients had a positive family anamnesis while the other two were sporadic. Genetic analysis was performed by the use of a standard protocol, which included PCR amplification and DNK sequencing according to the method of Senger and autoradiografy. Results. In the patients from the family DRD-1 new hetaerazygote point mutation 520G→A in 4-m exson gene GCH-I was revealed. First symptoms of the disease showed in the age of seven by the torsion of the left foot, progressively advanced and got into the evolution of numbness in the legs, aggravated gait, tending to worsen in the evening, and the therapy with levodopa (500 mg) produced a dramatic effect. The second mutation in the female patient from the family DRD-2 was homozygote deletion in1-m intron gene GCH-I (IVS1-85delA). Unwilling torsion of the foot, feeling of weakness in the lower extremities (that caused falling without loss of the consciousness) were clinical demonstrations of the disease. The application of levodopa (300 mg) caused regression of the symptoms of the disease. Hetaerazygote deletion of adenine in the position 209 in the first exon (209del A) was identificated in the patient DRD-3 with negative family anamnesis, in who in the age of ten the torsion of the foot inside occurred for the first time following by trembling of both the left and right legs at rest; after a few years, tremor of hands also appeared, which became worse in stressful situations. The father of the patient was an asymptomatic bearer of mutation. The fourth mutation in gene GCH-I was found in I exon gene GCH- I, 208delA. The disease was started by torsion of the left foot, progressing easily, and worsening in the evenings, but at the age of 30, moving became harder, fatigue and pain in muscles, increased and at the age of 40 the patient recognized the change of speech. The application of levodopa (300 mg/daily) made the patient feel better and walk independently. Conclusion. The study presented four patients with genetic confirmation of the diagnosis of dopa-responsive dystonia. This entity is very significant in differential diagnostics of both early dystonia (< 26 years) and early parkinsonism (< 40 years) since it can be successfully managed by applying relatively low doses of levodopa over a long period of time.